KECERDASAN BUATAN SEBAGAI PENINGKATAN LITERASI DIGITAL DI DINAS KOMUNIKASI DAN INFORMATIKA KAB. MUARO JAMBI - Darex Susanto; Khamsa Kamil (LP2M Universitas Nurdin Hamzah, 2026)
The effectiveness of artificial intelligence (AI) learning in efforts to improve digital literacy understanding in the Muaro Jambi Regency Communication and Informatics Office. This includes individuals who work in the environment. Digital Literacy is essential in the era of digital transformation, especially for government officials involved in information and technology governance as an unlimited understanding. The method used in this study is a qualitative descriptive study with a case study approach. Data were collected through observations, on the use of artificial intelligence (AI) in the scope of service both in carrying out tasks and public services that can provide efficient and effective problem solving. This illustrates that artificial intelligence learning is able to improve employee understanding of digital technology, data processing skills, and skills in using artificial intelligence (AI)-based devices in supporting public services. So the conclusion of this study is that the integration of artificial intelligence (AI) materials in the digital literacy understanding program has a positive impact on increasing the capacity of human resources in the field of regional communication and informatics.